Throughput analysis of the go-back-N protocol in fading radio channels. - Turin, W.
We derive a formula for calculating the throughput efficiency of the go-back-N (GBN) protocol when error sources in the forward and backward channels are modeled by a hidden Markov model. The result is presented in the matrix form which makes it applicable to models with any number of states. We consider also the relationship between bit-level and block-level models and obtain the probability distribution of the time that a message spends in the system
Keywords: CDMA cellular system; Backward channel; Bit-level model; Block-level model; Error sources; Fading radio channels; Forward channel; Go-back-N protocol; Hidden Markov model; Matrix; Probability distribution; Radio networks; Throughput analysis; Throughput efficiency